Quartermaster supplies, equipment and services during operations in extreme cold. - Sandlin, Joseph C. (Fort Leavenworth, KS : US Army Command and General Staff College, 1948)
This paper was written to study Quartermaster supplies and equipment for use in operations considering both mountain and sub-arctic where temperatures may be as low as minus twenty degrees (-20 F).